Interpretasi Kerangka Kerja UNESCO AI CFT pada pengembangan kompetensi AI guru - Yaziz Abi Sufyan; Deni Kurniawan (Curricula: Journal of Curriculum Development, 2026)
AI’s rapid development has transformed education, offering opportunities and challenges for teachers. Amid digital disruption, they must now act as value guides, learning facilitators, and guardians of humanity in classrooms as they share with intelligent technologies. This article analyzes UNESCO’s AI Competency Framework for Teachers (AI CFT) as a conceptual framework to guide teachers in mastering, critically engaging with, and creatively applying AI in ethical and meaningful ways. Using a document analysis approach to the text “Teachers’ Competencies in Using AI,” this study highlights five core dimensions of the AI CFT: a human-centered mindset, ethics of AI, AI foundations and applications, AI pedagogy, and AI for professional development. The findings indicate that AI competence is not merely a technical skill, but rather an expression of teachers’ moral and professional maturity in integrating technology with human values. The AI CFT thus serves as an essential guide to ensure that Indonesian teachers are not only users of technology, but also creators of meaning in humanistic, reflective, and socially just learning. The presence of AI should not obscure the role of teachers; instead, it should reaffirm their calling as educators who humanize the learning process amid the accelerating currents of digitalization.